Assessment of the therapeutic effect and subsequent immune response in the treatment of COVID-19 with anti-SARS-CoV-2 monoclonal antibodies - Petar Yordanov Atanasov; Yozlem Ali Kobakova; Maria Georgieva Moneva-Sakelarieva; Stefka Achkova Ivanova; Maria Sevdelinova Chaneva; Ventseslava Petrova Atanasova; Radoslav Fedeev Todorov; Nikolay Zarkov Bashev; Angelina Georgieva Kirkova-Bogdanova; Maria Vakrilova Becheva (Pharmacia)
Introduction: Over the past three decades, monoclonal antibodies have undergone a remarkable transformation—from a research tool to powerful therapeutic agents in medical practice. The monoclonal antibodies currently used in clinical practice are immunoglobulins of the “G” class (IgG). Objective: The aim of the study is to analyze and evaluate the effect of treatment with monoclonal anti-SARS-CoV-2 IgG in patients with moderate to severe forms of complicated coronavirus infection. Materials and methods: The study included 530 patients, of whom 243 were women and 287 were men, aged between 18 and over 80 years, who received monoclonal antibodies (mAbs) as part of their therapeutic regimen for the treatment of COVID-19. In parallel with them, the course of the disease was monitored in a control group of 255 patients (104 women and 151 men), hospitalized in the target period and not treated with mAbs. Results: Patients treated with monoclonal antibodies within 7 days of symptoms had a shorter hospital stay compared to those treated later and to the control group. Oxygen therapy and intubation rates were significantly lower for those who received treatment early. Mortality rates were 0.42% for early treatment, 3.45% for late treatment, and 4.71% in the control group. Conclusion: Specific monoclonal antibodies are currently the most effective safe treatment for life-threatening viral infections, supporting passive immunization as a preferred strategy against epidemics. A strong immune response is evident in treated patients by the end of the first year post-discharge. Early administration significantly reduces mortality compared to controls.